Rezeption kritischer Perspektiven auf postkoloniale Theorie - Freuding, Janosch (Österreichisches Religionspädagogisches Forum, 2023)
Postcolonial approaches have only recently been more widely received in German-language religious education. In this reception, it is important to also take into account points of criticism of postcolonial theory. This article offers an overview of relevant critical perspectives – and, against this background, sheds light on existing potentials for religious education processes.